Preventing domestic violence through integrated community work - Silven-Savigñón, Bárbara Mailén; Machuca-Fernández, Larissa; Rivero-Favier, Meglis; Zambrano-Barberan, María Fernanda; Sornoza-Menéndez, Carlos Eduardo (International research journal of management, IT and social sciences, 2025)
This study is methodologically based on the qualitative research paradigm, with a descriptive approach. It allowed us to investigate, describe, and evaluate the prevention of domestic violence carried out by the multidisciplinary team in the community of San Justo, in the Guantánamo municipality. The participatory action research method was used to determine the level of preparation of the 12 members of the multidisciplinary team to carry out preventive work through integrated community outreach, from January to July 2025. The empirical methods used were participant observation, in-depth interviews, document review, questionnaires, and triangulation. Shortcomings were revealed in the level of integration of this group in the prevention of domestic violence. The need to enhance their training in socioemotional skills and sociopsychological resources for the most effective development of their work was noted. The viability of psychoeducational interventions was confirmed as a useful alternative for the preventive work carried out by this multidisciplinary team in addressing this social problem.